Education on the Role of Mangroves in Increasing the Potential of Muaragembong Community Ponds, West Java - Ameilia Zuliyanti Siregar; Oding Affandi; Basyuni Basyuni; Bejo Slamet; OK Hasnanda; Masitta Tanjung; Yaya Ilhamuddin; Suyadi Suyadi; Irmayeny Irmayeny; Virni Budi Arifanti; Sri Suharti; Yulizar Rahmila; Mira Yulianti (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program was conducted by the PUI Mangrove USU and PKR Mangrove Ecology PREE BRIN teams in Muaragembong District, Bekasi Regency, West Java on October 26, 2024. The aim was to raise awareness and support the conservation of mangrove ecosystems to improve community pond productivity. Primary data were collected through field observations, interviews, and purposive sampling of 12 members of the KTH Sumber Makmur group. Activities included planting 10,000 Rhizophora mucronata and Avicennia sp. seedlings, educational outreach, and focus group discussions on mangrove functions in environmental protection and socio-economic development. The silviforestry approach, integrating fish, shrimp, and seaweed cultivation in mangrove ecosystems, has increased production while maintaining water quality. Planned mangrove ecotourism development offers further economic potential if supported by local regulations. These efforts are expected to improve ecosystem sustainability and local welfare.